Implementasi Sistem Manajemen Hotel Berbasis Android: Studi Kasus Habibah Syariah Hotel - Usman, Adam; Susilo, Joko (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Technological developments have made many aspects of life easier, including education, business and the economy. However, several sectors in the business sector still face challenges in adopting technology, causing difficulties in data management and decision making. To overcome this problem, an application system for recording hotel room availability was developed using Android Studio and phpMyAdmin. This research uses a qualitative approach with a focus on analyzing the availability of room data at the Habibah Syariah Hotel. The result is an Android-based application and web database that makes it easier for management and staff to manage information regarding room availability, increases recording efficiency, and reduces the risk of data loss.